Interventions to minimise doctors' mental ill-health and its impacts on the workforce and patient care: the Care Under Pressure realist review - Daniele Carrieri; Mark Pearson; Karen Mattick; Chrysanthi Papoutsi; Simon Briscoe; Geoff Wong; Mark Jackson (National Institute for Health Research, 2020)
Background: The growing incidence of mental ill-health in health professionals, including doctors, is a global concern. Although a large body of literature exists on interventions that offer support, advice and/or treatment to sick doctors, it has not yet been synthesised in a way that takes account of the complexity and heterogeneity of the interventions, and the many dimensions (e.g. individual, organisational, sociocultural) of the problem. Objectives: Our aim was to improve understanding of how, why and in what contexts mental health services and support interventions can be designed to minimise the incidence of doctors' mental ill-health. The objectives were to review interventions to tackle doctors' mental ill-health and its impact on the clinical workforce and patient care, drawing on diverse literature sources and engaging iteratively with diverse stakeholder perspectives to produce actionable theory; and recommendations that support the tailoring, implementation, monitoring and evaluation of contextually sensitive strategies to tackle mental ill-health and its impacts. Design: Realist literature review consistent with the Realist And Meta-narrative Evidence Syntheses: Evolving Standards quality and reporting standards. Data sources: Bibliographic database searches were developed and conducted using MEDLINE (1946 to November week 4 2017), MEDLINE In-Process and Other Non-indexed Citations (1946 to 6 December 2017) and PsycINFO (1806 to November week 2 2017) (all via Ovid) and Applied Social Sciences Index and Abstracts (1987 to 6 December 2017) (via ProQuest) on 6 December 2017. Further UK-based studies were identified by forwards and author citation searches, manual backwards citation searching and hand-searching relevant journal websites. Review methods: We included all studies that focused on mental ill-health; all study designs; all health-care settings; all studies that included medical doctors/medical students; descriptions of interventions or resources that focus on improving mental ill-health and minimising its impacts; all mental health outcome measures, including absenteeism (doctors taking short-/long-term sick leave); presenteeism (doctors working despite being unwell); and workforce retention (doctors leaving the profession temporarily/permanently). Data were extracted from included articles and the data set was subjected to realist analysis to identify context-mechanism-outcome configurations. Results: A total of 179 out of 3069 records were included. Most were from the USA (45%) and had been published since 2009 (74%). More included articles focused on structural-level interventions (33%) than individual-level interventions (21%), but most articles (46%) considered both levels. Most interventions focused on prevention, rather than treatment/screening, and most studies referred to doctors/physicians in general, rather than to specific specialties or career stages. Nineteen per cent of the included sources provided cost information and none reported a health economic analysis. The 19 context-mechanism-outcome configurations demonstrated that doctors were more likely to experience mental ill-health when they felt isolated or unable to do their job, and when they feared repercussions of help-seeking. Healthy staff were necessary for excellent patient care. Interventions emphasising relationships and belonging were more likely to promote well-being. Interventions creating a people-focused working culture, balancing positive/negative performance and acknowledging positive/negative aspects of a medical career helped doctors to thrive. The way that interventions were implemented seemed critically important. Doctors needed to have confidence in an intervention for the intervention to be effective. Limitations: Variable quality of included literature; limited UK-based studies. Future work: Use this evidence synthesis to refine, implement and evaluate interventions. Study registration: This study is registered as PROSPERO CRD42017069870. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 19. See the NIHR Journals Library website for further project information.